Competition Law in Asia - Srivastava, Ankit; Tiwary, Aditi Richa (Lentera Hukum, 2021)
The digital economy and multi-faceted markets have significantly contributed to the efficacy of most transactions governing modern humankind. Digital platforms have become an irreplaceable cross-border asset that has acclimatized with technological advancements. However, there is obscurity in the methods of accommodation of digital economy in competition laws of most jurisdictions globally. Consequently, there are ascertainable issues in competition laws of such jurisdictions. Such issues remain unaddressed due to the absence of evaluation parameters of digital platforms in the conventional market system and culminate into an Implicit and undetected abuse of dominance. This study used the doctrinal method by highlighting the distinctness of contemporary digital markets and their consequential issues. This study explicated the issues in the competition that need to be independently addressed, considering the intricacies of digital platforms. The presence of non-price factors, multi-faceted markets, and data-driven networks being the primary source of such novel issues have been particularly explicated. The established premise was substantiated by way of case studies of major events involving factors such as predation, deep discounting, and data privacy. Elucidation of the competition system in most jurisdictions in Asia and the accommodation of digital platforms in the same was also sufficiently enunciated to present a holistic insight to the established premise. Finally, the authors suggested ways to sufficiently address the issues arising from the distinctness of digital platforms, thereby giving rise to a dynamic and all-inclusive competition. KEYWORDS: Digital Markets, Competition Law, Data Privacy.